Remaining Service Life Struktur Conveyor D pada Tambang Batubara PT XYZ di Kabupaten Banjar, Provinsi Kalimantan Selatan - Eldera Rizki Nuraini; Elfida Moralista; Iswandaru (UNISBA Press, 2022)
Abstract. In the mining industry, one of the activities involved is the moving of mining materials that requires transport equipment to move materials effectively and efficiently. The tool used is the conveyor. This conveyor is based on carbon steel that is susceptible to corrosion result of environmental factors, such as the rainfall and moisture from the surrounding areas. Because of corrosion, it could result in a reduced life span in the conveyor structure. Therefore there was a parallel control and monitoring of corsicles in the conveyor structure by preventing corrosion reactions on the surface of the conveyor structure in order to increase the production of the excavated materials in the research area. The study was to know the types of corrosion, the methods of corrosion control, and the residual age wore on the surface of the conveyor structure. The research methodology used is the method of measuring the thickness of a conveyor structure by using an Ultrasonic Thickness Gauge TT 130. The study was carried out in 90 meter long conveyor structure which is divided into 3 segments with 25 test points. For environmental conditions in the research area, the 2016 - 2020 average rainfall is 261.791 mm/year, the average air temperature in 2017 - 2021 is 28.63°C and the average relative humidity in 2016 - 2020 by 77.54%. The type of corrosion that occurs on the surface of the conveyor structure is uniform corrosion. The method used for corrosion control is the coating method with a 3 layer system, namely the Seaguard 5000 primer coating, Sherglass FF intermediate coating and the Aliphatic Acrylic Modified Polyurethane top coating. The corrosion rate that occurs in the conveyor structure is in the range of 0.1833 – 0.3483 mm/year. The type of corrosion is categorized as good based on the relative corrosion resistance of steel. Meanwhile, the service life of the conveyor structure is 6 years and the remaining service life is around 6.42 – 9.36 years. Thus, there are 13 test points or 52% which are predicted not to reach the design life of 15 years. Abstrak. Dalam industri pertambangan, salah satu kegiatan yang dilakukan yaitu pemindahan material tambang yang membutuhkan alat angkut untuk memindahkan material secara efektif dan efisien. Alat yang digunakan yaitu conveyor. Conveyor ini berbahan dasar baja karbon yang rentan mengalami korosi akibat dari faktor lingkungan sekitar, seperti curah hujan dan kelembaban dari daerah sekitarnya. Dengan terjadinya korosi maka dapat mengakibatkan berkurangnya sisa umur pakai pada struktur conveyor. Oleh karena itu maka diperlukan pengendalian serta monitoring korosi pada struktur conveyor dengan cara mencegah reaksi korosi pada permukaan struktur conveyor agar dapat meningkatkan produksi dari bahan galian yang berada di daerah penelitian. Penelitian ini bertujuan untuk mengetahui jenis korosi, metode pengendalian korosi, dan sisa umur pakai pada permukaan struktur conveyor Metodologi penelitian yang digunakan adalah metode pengukuran pengurangan ketebalan struktur conveyor dengan menggunkaan alat Ultrasonic Thickness Gauge TT 130. Penelitian ini dilakukan pada struktur conveyor sepanjang 90 meter yang dibagi menjadi 3 segmen dengan 25 test point. Untuk kondisi lingkungan yang berada di daerah penelitian memiliki curah hujan rata-rata 2016 - 2020 sebesar 261,791 mm/tahun, temperatur udara rata-rata pada tahun 2017 - 2021 sebesar 28,63°C dan kelembaban relatif rata-rata pada tahun 2016 - 2020 sebesar 77,54%. Jenis korosi yang terjadi pada permukaan struktur conveyor yaitu korosi merata. Metode yang digunakan untuk pengendalian korosi yaitu dengan menggunakan metode coating dengan sistem 3 layer yaitu primer coating Seaguard 5000, intermediate coating Sherglass FF dan top coating Aliphatic Acrylic Modified Polyurethane. Laju korosi yang terjadi pada struktur conveyor yaitu berkisar antara 0,1833 – 0,3483 mm/tahun. Jenis korosi termasuk kategori good berdasarkan ketahanan korosi relatif baja. Sedangkan untuk umur pakai struktur conveyor yaitu 6 tahun dan sisa umur pakai berkisar 6,42 – 9,36 tahun. Dengan demikian terdapat 13 test point atau 52% yang diprediksi tidak dapat mencapai umur desain yaitu 15 tahun.